Profile of care given to burn injured patients during the first 48 hours in the Princess Marina Hospital (Botswana) - Dithole, Kefalotse S. (My University, 2014)
Burns are a problem throughout the world and in most cases the victims are children and young adults. Monitoring of the patient’s physiological parameters collected adequately through health history and skilful physical assessment are important in arriving at meaningful decisions when managing burn injured patients. The study aimed at describing what health care providers do in order to manage burn injured patients during the first 48 hours post burn injury. A descriptive survey using a checklist was used to obtain data. The population consisted of all records of patients admitted to and/or treated for burn injury over a one year period in the Princess Marina hospital in Gaborone. The records of 78 burn injured patients were selected. Computer analysis, after data was coded, was utilized. Narrative and descriptive statistics were used to present the information from the checklist. The study showed that important information on health history and physical assessment was omitted and this resulted in inadequate management of burn injured patients. The major findings were as follows: Very few (8%) of patients with burns were weighed or weight estimated on admission. The use of the rule of nine in adults and the Lund and Browder chart for children were not used for estimation of the extent of bum injury yet burn injury was classified according to degree and percentage of total body surface area. Fluid was not adequately replaced as a Huid formula was not used. Few patients (10%)had complications at the ena of the Irst 48 hours and only one patient died. The findings of this study indicated that fluid formulas were nnt used and the extent of the burn injury was not estimated using the rule of nine or the Lund and Browder chart. The health history and physical assessment ’-'as not adequately done.